A Study on Corporate Governance and Business Ethics-Indian Scenario - Das, Dr Pradip Kumar (Advances in Social Sciences Research Journal, 2018)
Frequent corporate frauds and governance failures dotting the global corporate map have witnessed comparably vigorous efforts of improving corporate governance practices. India has liberalized the regulatory fabric of the country to align her corporate governance norms with those of developed countries. And yet, achieving good governance and ensuring results of such governance practices continue to remain one of the top priorities of stakeholders even today. High profile scandals resulting in financial collapses have served as the impetus for most sweeping corporate governance practices for bringing economic viability to the nations. Abuse of authority by a particular group of stakeholders continues to influence the corporate choices to the extent stakeholders. Governance is no longer treated as a set of rules concerning the management of firm; rather, it would establish diverse rights and obligations to reduce the negative externalities of an economic entity. By this paper, the author intends to explain the gap between corporate governance reforms and ethics and to seek why these two movements seem yet to be generated little in the form of widely accepted prescriptions for improvement of business behavior to the satisfaction of the constituents of business. The implication of the study showcases conduct, measures to be taken to induce compliance with provisions of the code. It also suggests as to how regulatory bodies should deal with corporate overcoming the weaknesses concerning the way they conceive modern business operations in the event of non-compliance by corporate. Keywords: Corporate governance, Business ethics, Business operation, Corporate, Stakeholders